KANDUNGAN INFORMASI PADA PENGUMUMAN REVERSE STOCK SPLIT - I Putu Sugiartha Sanjaya (Journal of Management and Business, 2007)
The objective of this study is to investigate whether market reacts to reverse stock split announcement. If market reacts to the announcement therefore the announcement has information content and vice versa. Reverse stock split is an interesting issue regarding financial policies. The study uses companies listed in Jakarta Stock Exchange (JSX) announcing reverse stock split. The research uses data from 2001 to 2007, because several companies informs reverse stock split to the market during the period. This study expects that the announcement have a market reaction. The result of this study is market reacts to the announcement. Therefore, the announcement of reverse stock split has information content.